USING THE EXPERIMENTATION FOR SOLVING PROBLEMS IN SCHOOL MATHEMATICS - ANTOŠ, Karel (Trends in education, 2016)
Article Using experimentation for solving problem in school mathematics wants to show how the method called research approach can be involved to the teaching of school mathematics. It shows how experimentation can be used in the research approach and how the experimentation can be used for exploring mathematical situations or possibly for solving mathematical problems. Using this method we can teach pupils and students to solve problems by themselves, or in the case of mathematical situations to explore them. Pupils and students can get to know the creative aspect of mathematics as a way to finding solutions to mathematical problems. The aim is to show the research approach as a method by which students can discover new knowledge and teach themselves. Using experimentation is shown by the examples exploring mathematical situations and solving two mathematical problems.
Keywords: experimentation; mathematical situation; problem; proof; Fibonacci sequence; the greatest common divisor